Matrix‐free room‐temperature phosphorescence graphitic carbon nitride quantum dots based on halogen bond interactions for security applications. Issue 2 (23rd June 2021) - Kong, Yuelin; He, Yu; Wang, Yaping; Song, Gongwu
Abstract: Herein, we first designed a one‐step strategy to achieve matrix‐free room temperature phosphorescence (RTP) materials by low temperature solid phase synthesis, using sodium citrate as carbon source and urea as nitrogen source. The NaF, NaCl, NaBr, and NaI were chosen as the inducer source of halogens to effective trigger the RTP emission from graphitic carbon nitride quantum dots (CNQDs) denoted F‐CNQDs, Cl‐CNQDs, Br‐CNQDs and I‐CNQDs. All the doped‐CNQDs emitted bright fluorescence upon 365 nm irradiation. After the 365 nm UV lamp is off, only the Br‐CNQDs showed green phosphorescence which can be observed by naked eye. The phosphorescence emission of Br‐CNQDs is excitation‐dependent from 510 to 610 nm with the average RTP lifetime of 70 milliseconds, which indicated Br‐CNQDs could exhibit color‐tunable phosphorescence. When 365 nm UV is off, Br‐CNQDs emitted green afterglow for about 3 seconds observed naked eye, while the Br‐CNQDs presented visible yellow afterglow for about 3 seconds with ceasing off 395 nm irradiation. The absolute phosphorescence quantum yield (PQY) of the Br‐CNQDs powder reaches up to 3.64%. Thus, the color change and long lifetime of phosphorescence from the excitation‐dependent feature could provide a security application for counterfeiting and information protection systems. Abstract : Schematic illustration of the synthesis of RTP CNQDs. Photographs of the RTP CNQDs under UV lamp (λ = 365 and 395 nm) on and off.